(untitled) (Jurnal Abdimas Administrasi Kesehatan, 2021)
An alternative problem-solving framework is carried out by providing this assistance so that the health administration in participating in running the stunting-free Indonesia program. The purpose of this assistance is to provide an ease for the health administration to play a role in running the stunting-free Indonesia program at the Juanda Health Center. The community service method is in the form of training on the preparation of an annual work plan at the Juanda Health Center as many as 15 people. Medical record structuring training through label coloring at the Juanda Health Center is proven by directly 100% categorized as good